Hospital-Based Management of High-Risk Patients with Cardiopulmonary Arrest in Children-An Updated Review for Nursing, Respiratory therapy, Health administration, Services management, and Medical secretarial services - Alrasheedi, Mohammad Saad Saud Alrasheedi; Abdulkarim Marzooq Awad Alhejaili,; Abdullah Break Salim Alhazmi,; Alaa Abdullah Mohammed Msmali,; Saad Duhime Aldawsari,; Seham Ibrahim Abdullah Alhuwaymil,; Hana Saeed Faqih,; Walaa Homad Mohammed Hakami, (Saudi Journal of Medicine and Public Health, 2025)
Background: Pediatric cardiopulmonary arrest remains a major cause of morbidity and mortality, with over 20,000 cases annually in the United States. Respiratory failure, hypovolemia, sepsis, trauma, and congenital cardiac abnormalities are the leading etiologies in children. Early recognition, high quality CPR, and adherence to Pediatric Advanced Life Support (PALS) guidelines significantly improve outcomes. Aim: This review aims to summarize updated hospital based management strategies for high risk pediatric patients experiencing cardiopulmonary arrest, highlighting etiology, pathophysiology, evaluation, and evidence based treatment. Methods: A comprehensive narrative review approach was applied, integrating current AHA and PALS guidelines, epidemiologic data, and clinical management frameworks. Key topics include arrest physiology, rhythm classification, reversible causes, and advanced resuscitation techniques. Results: Respiratory etiologies account for approximately 75% of pediatric arrests. Survival varies widely by location: in hospital survival approaches 24–40% compared with 5–8% for out of hospital events. Early CPR, rapid defibrillation for shockable rhythms, and correction of reversible causes significantly improve return of spontaneous circulation (ROSC). Defibrillation with biphasic shocks and timely epinephrine remain central to management. Post resuscitation care—including ventilation optimization, hemodynamic stabilization, and neuroprotection—is essential for improving neurological outcomes. Conclusion: Pediatric cardiopulmonary arrest demands immediate recognition, high quality CPR, and structured evaluation using the ABCDE approach. Survival strongly depends on early interventions, rapid rhythm identification, and targeted management of reversible causes. Strengthening team coordination, improving caregiver and public CPR education, and enhancing hospital preparedness are vital for improving outcomes.